Primary Biliary Cholangitis Alters Functional Connections of the Brain's Deep Gray Matter. Issue 7 (July 2017) - Mosher, Victoria A L; Swain, Mark G; Pang, Jack X Q; Kaplan, Gilaad G; Sharkey, Keith A; MacQueen, Glenda M; Goodyear, Bradley G
Abstract : OBJECTIVES: : Fatigue, itch, depressed mood, and cognitive impairment significantly impact the quality of life of many patients with primary biliary cholangitis (PBC). Previous neuroimaging studies of non‐hepatic diseases suggest that these symptoms are often associated with dysfunction of deep gray matter brain regions. We used resting‐state functional magnetic resonance imaging (rsfMRI) to determine whether PBC patients exhibit altered functional connections of deep gray matter. METHODS: : Twenty female non‐cirrhotic PBC patients and 21 age/gender‐matched controls underwent rsfMRI. Resting‐state functional connectivity (rsFC) of deep gray matter brain structures (putamen, thalamus, amygdala, hippocampus) was compared between groups. Fatigue, itch, mood, cognitive performance, and clinical response to ursodeoxycholic acid (UDCA) were assessed, and their association with rsFC was determined. RESULTS: : Relative to controls, PBC patients exhibited significantly increased rsFC between the putamen, thalamus, amygdala, and hippocampus, as well as with frontal and parietal regions. Reduced rsFC of the putamen and hippocampus with motor and sensory regions of the brain were also observed. Fatigue, itch, complete response to UDCA, and verbal working memory performance were also associated with altered rsFC of deep gray matter. These rsFC changes were independent of biochemical disease severity. CONCLUSIONS: : PBC patients have objective evidence of altered rsFC of the brain's deep gray matter that is in part linked to fatigue severity, itch, response to UDCA therapy, and cognitive performance. These results may guide future approaches to define how PBC leads to altered brain connectivity and provide insight into novel targets for treating PBC‐associated brain dysfunction and behavioral symptoms.